Thermal asymmetries in striking combat sports athletes measured by infrared thermography - del Estal, A.; Brito, C.-J.; Galindo, V.-E.; Lopez Diaz de Durana, A.; Franchini, E.; Sillero-Quintana, M. (Science & Sports, 2017)
Background: In striking combat sports athletes, the most common injuries occur in lower extremities and head, and prevention methods are needed to improve athletes` training and competition performance. Objective: The aim of this study was to investigate the thermal profile and asymmetries lead vs. rear side in kickboxing and Muay Thai athletes. Material and methods: In a transversal design, fifteen athletes of kickboxing and Muay Thai (MT) (age: 23.3 ± 3.4 years, training experience: 4.9 ± 3.4 years, height: 1.8 ± 0.1 m, body mass: 68.1 ± 6.5 kg and BMI: 21.0 ± 1.5 kg/m2) had their temperature measured by infrared thermography (IRT). Results: The results indicated symmetry concerning lead vs. rear except by the higher (P <; 0.05) rear temperature on abdomen (+0.5 °C), lumbar (+0.4 °C), calf (+0.4 °C) (P < 0.05) compared to lead, and higher values (P < 0.05) for lead shinbone (+0.4 °C) and knuckle (+0.3 °C) compared to rear. Conclusion: We believe that the possible cause of these asymmetries may be the repeated strikes and the specific muscle actions during the combat.